Remote ischaemic conditioning for efficacy in patients with aneurysmal subarachnoid haemorrhage (REPAIR): protocol for a multicentre, randomised, double-blind, sham-controlled, parallel-group trial - Yunjian Yin; Xunming Ji; Aihua Liu; Xin Feng; Hao Niu; Lan Liu; Wenbo Zhao; Tonghu Jin; Liuyu Xu; David C Hess (BMJ Open)
Introduction A large number of basic and clinical studies have demonstrated that remote ischaemic conditioning (RIC) has neuroprotective effects. Recently, RIC has made gratifying progress in the field of ischaemia stroke treatment. A considerable number of basic and clinical studies have also revealed the possible therapeutic effects of RIC on subarachnoid haemorrhage. However, the neuroprotective effect of RIC on subarachnoid haemorrhage is still lacking convincing evidence and deserves further study.Aim To explore the efficacy and safety of RIC for aneurysmal subarachnoid haemorrhage.Methods and analysis An investigator-initiated, multicentre, randomised, double-blind, sham-controlled, parallel-group trial to evaluate the effect of RIC intervention compared to sham RIC intervention for the neurological function improvement of patients with aneurysmal subarachnoid haemorrhage.Ethics and dissemination The protocol was approved by the IRB of Beijing Tiantan Hospital, Capital Medical University (KY2024-080-03). Progress and safety of the trial are monitored by an independent Data and Safety Monitoring Board. Study results will be published in peer-reviewed medical journals. Written informed consent will be obtained from all participants.Trial registration number NCT06711302.